From confusion to fun: Box Fraction Media for better understanding of fractions - Putri, Karin Hernelia; Azizah, Farhatul; Kamelia, Nabila Putri; Stiven, Jepri; Susanti, Elsa; Zulkardi, Zulkardi; Mulyono, Budi; Meryansumayeka, Meryansumayeka (Universitas Terbuka, 2025)
Students' low understanding of fractions is a major obstacle to achieving basic mathematical competence at the primary school level. To address this issue, innovative, engaging, and easy-to-understand learning media are required to help students grasp fraction concepts more effectively. This study aims to design and evaluate a participatory and interactive game-based learning medium called Box Fraction Fun. The Research and Development (R&D) method was employed, using the ADDIE model. Validation by two subject matter experts and two media experts showed that the medium was considered suitable to highly suitable based on a four-level suitability scale. Practicality was assessed through questionnaires given to three fourth-grade students and one teacher at a public elementary school in Bukit Lama district, Palembang, with results indicating that the medium was “very practical.” The effectiveness of the medium was evaluated using pre-test and post-test scores analyzed with N-gain calculations, which demonstrated significant improvement in students’ understanding of fractions. These findings suggest that Box Fraction Fun is highly valid, practical to use, and effective in supporting students’ learning. Theoretically, this study contributes to the literature on the development of interactive game-based mathematics learning media. Practically, it provides teachers with an innovative and effective tool to enhance students’ understanding of fractions.